Fraud Triangel: Menggali Akar Kecurangan dalam Etika Islam - Wati, Sulaiha; Hirman, Akhmad Akram; Hamidah; Hutabarat, Devi Natalia (Jurnal Ilmiah Ekonomi Islam, 2025)
The Fraud Triangle theory consists of three elements, namely Pressure, Opportunity, and Rationalization, which are integrated with the concept of human vices, according to Imam Al-Ghazali's book Ihya Ulumuddin. This research aims to understand the factors that drive a person to commit fraud, focusing on how vices such as Sabu'iyah, Bahimiyyah, and Syaithaniyah contribute to cheating behaviour. This research uses a qualitative method with semi-structured interviews with informants from manufacturing companies and tax consulting services in Indonesia. The results showed that the three elements of the Fraud Triangle, namely Opportunity, Rationalization, and Pressure, which are integrated with the book of Ihya Ulumuddin Imam Al-Ghazali that a person will commit fraud because of his nature, does not have a firm stance and faith. The weakness of an internal control system that causes a person to bring up his greed (Sabu'iyah), impulsive actions (Bahimiyah), and Mand guidance (Syaithaniyah) sees an opportunity. This pressure exists so that it rationalizes what is not good. The research results can strengthen a good internal control system for the company, employee ethics and morals, and a positive organizational culture. Novelty This research approach offers a new perspective on understanding the causes of fraud in financial statements through spiritual and ethical lenses that are rarely raised in the literature on fraud.